Continuous local antibiotic perfusion for patients with surgical site infection after instrumented spinal surgery; a novel technique to retain the implants. (November 2021) - Takahashi, Hiroshi; Koda, Masao; Funayama, Toru; Noguchi, Hiroshi; Miura, Kousei; Mataki, Kentaro; Shibao, Yosuke; Eto, Fumihiko; Kono, Mamoru; Sato, Kosuke; Asada, Tomoyuki; Okuwaki, Shun; et al.
Highlights: CLAP was applied to 4 continuous patients who developed SSI after instrumented spinal surgery. CLAP controlled the SSIs without severe adverse events and enabled retention of the implants. CLAP may become an option for the treatment of SSIs after instrumented spinal surgery. Abstract: Objectives: To describe the novel technique of continuous local antibiotic perfusion (CLAP) for a surgical site infection (SSI) after instrumented spinal surgery. Methods: CLAP was applied to 4 continuous patients at our institution who developed SSI after instrumented spinal surgery. Results: All 4 patients were successfully treated and the infection was controlled. The implant was retained in all patients. The duration of CLAP ranged from 2 to 3 weeks. The blood level of the antibiotic used (gentamicin) at 1 week after the initiation of CLAP did not increase in any patient. No other adverse events occurred in any patient. Dramatic improvements in laboratory parameters, including the white blood cell (WBC) counts and C-reactive protein (CRP) levels were seen in every patient at 1 week after the initiation of CLAP. Conclusions: CLAP controlled the infection without severe adverse events in all 4 patients, and the implants were retained. Despite its cost and the discomfort of patients, CLAP may become an option for the treatment of SSIs after instrumented spinal surgery. A large number of case series are needed to verify the efficacy of CLAP for patients with SSIs after instrumented spinal surgery.